2008
DOI: 10.1021/pr7008109
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Proteomic Biomarkers in Breast Cancer by Laser Capture Microdissection and MALDI MS

Abstract: We assessed proteomic patterns in breast cancer using MALDI MS and laser capture microdissected cells. Protein and peptide expression in invasive mammary carcinoma versus normal mammary epithelium and estrogen-receptor positive versus estrogen-receptor negative tumors were compared. Biomarker candidates were identified by statistical analysis and classifiers were developed and validated in blinded test sets. Several of the m/z features used in the classifiers were identified by LC-MS/MS and two were confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 44 publications
0
44
0
1
Order By: Relevance
“…Laser capture microdissection is often used in conjunction with MS-based protein identification technology to assist with the discovery of tumor-associated molecules in tissue specimens containing various types of cells (27,31,(61)(62)(63)(64). However, relatively few studies have used these techniques to identify OSCC/HNSCC-associated proteins in tissue specimens from patients with OSCC/HNSCC (15,17,29).…”
Section: Discussionmentioning
confidence: 99%
“…Laser capture microdissection is often used in conjunction with MS-based protein identification technology to assist with the discovery of tumor-associated molecules in tissue specimens containing various types of cells (27,31,(61)(62)(63)(64). However, relatively few studies have used these techniques to identify OSCC/HNSCC-associated proteins in tissue specimens from patients with OSCC/HNSCC (15,17,29).…”
Section: Discussionmentioning
confidence: 99%
“…Using LCM, Umar et al [24] detected 9 differentially expressed tryptic peptides (not structurally identified) following analysis of stromal and tumour cells collected from five tissue specimens. In addition, Sanders et al [23] identified ubiquitin and S100-A8 to be decreased in tumour (n = 122) compared to normal tissue (n = 167), whereas S100-A6 was found increased. Their split-sample approach allowed a successful within-study validation of the three potential markers [23].…”
Section: Protein Profiling Of Tissuementioning
confidence: 97%
“…In addition, Sanders et al [23] identified ubiquitin and S100-A8 to be decreased in tumour (n = 122) compared to normal tissue (n = 167), whereas S100-A6 was found increased. Their split-sample approach allowed a successful within-study validation of the three potential markers [23]. As both ubiquitin and S100-A6 were also found to decrease in lysates of human breast cancer cell lines following chemotherapy induced apoptosis [25], these proteins may provide insight into the pathogenesis of breast cancer upon further investigation.…”
Section: Protein Profiling Of Tissuementioning
confidence: 97%
See 1 more Smart Citation
“…The microdissected tissues are dropped on a MALDI target and directly covered by the MALDI matrix (PalmerToy et al, 2000;Xu et al, 2002). This approach was already used in order to classify breast cancer tumor types (Sanders et al, 2008), identify intestinal neoplasia protein biomarkers (Xu et al, 2009), and to determine differential profiles in glomerulosclerosis (Xu et al, 2005).…”
Section: Laser Capture Microdissection (Lcm)mentioning
confidence: 99%